Sexuality, fertility, family planning, family life, and partnership in young breast cancer patients: a longitudinal study - Jäkel, Karoline; Richter, Diana; Leuteritz, Katja; Sender, Annekathrin; Hinz, Andreas (Frontiers in Psychology, 2023)
Objectives: Adolescent and young adult (AYA) breast cancer patients are often faced with problems affecting their sexuality, fertility, family planning, family life, and partnerships. Since health care providers are often unfamiliar with problems specific to AYA cancer patients or hesitate to speak with patients about sexuality and fertility, this topic is insufficiently researched and too little integrated into routine oncological care. Methods: A total of 139 AYA breast cancer patients were surveyed twice, one year apart. Multiple questions were asked about satisfaction with sexuality, fertility, family planning, family life, and corresponding supportive care needs in these domains. Results: While the patients were largely satisfied with their family life and partnerships, they were less satisfied with their sexuality and family planning. Only small mean score changes were observed in these variables over the course of a year. Being a parent already and having the possibility of further completing family planning were strongly associated with higher satisfaction and lower supportive care needs in these domains. Satisfaction was generally negatively associated with supportive care needs. Older age was predictive of lower satisfaction with sexuality at follow-up. Conclusion: AYA cancer patients deserve special consultations concerning the impact of cancer and treatment on their sexuality and fertility, and it is especially important that women who have yet to complete their family planning be actively offered information and support concerning sexuality and fertility protection before beginning treatment.